Why do doctors kill themselves? A brief communication - Rolim Neto, Modesto Leite; Lima, Nádia Nara Rolim (Avanços em Medicina, 2025)
Background: Current evidence highlights that although it is a universal disease, depression and mental and behavioral disorders affect different careers differently. In this clinical context, studies consider that it is vitally important that we take action now to fully understand the actual impact of suicide on physician workforce. Objective: Here we show that the suicide rate among physicians has exploded in recent decades. The suicide rate among male and female physicians is 1.41 and 2.27 times higher than that of the general male and female population, respectively. Results: Suicide in doctors can be affected by intense competition. Other contributors include financial pressures, as well as the need to adjust to being “average” among their high achieving cohorts. Moving frequently between hospitals and wards on placement can generate anxiety too. There can be additional pressure to author publications and other CV-building achievements from early on in medical school. Conclusion: Despite the fact that 10-20% of them have suffered from depression, and suicide rates are reported to be much higher than among other professional groups or the general population, doctors have poor access to mental health care. The idea of giving up life comes when worries, fatigue, and emotional pain pile up on a level that makes doctors feel incapable of bearing that suffering.